2015
DOI: 10.1007/s13277-015-3282-9
|View full text |Cite
|
Sign up to set email alerts
|

Activation of matrix metalloproteinase-9 (MMP-9) by neurotensin promotes cell invasion and migration through ERK pathway in gastric cancer

Abstract: Neurotensin (NT) is distributed throughout the brain and gastrointestinal tract. Although the relationship between NT and matrix metalloproteinase-9 (MMP-9) activity in gastric cancer has not been reported, the elevation of MMP-9 and NT is reported in the breast, lung, prostate, and gastric cancer. The aim of our study is to investigate the relationship between NT and MMP-9 activity and the underlying signaling mechanism in gastric cancer cell lines. Commercial ELISA kits were used for estimation of NT and MMP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
50
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 35 publications
5
50
0
Order By: Relevance
“…NTS also participates in tumor migration and invasion. In prostate cancer, NTS stimulates tumor invasion rather than growth [20, 21]. However, the expression of NTS in HCC has been rarely explored because NTS is absent in healthy adult liver.…”
Section: Introductionmentioning
confidence: 99%
“…NTS also participates in tumor migration and invasion. In prostate cancer, NTS stimulates tumor invasion rather than growth [20, 21]. However, the expression of NTS in HCC has been rarely explored because NTS is absent in healthy adult liver.…”
Section: Introductionmentioning
confidence: 99%
“…5A and B, OZ treatment significantly reduced the invasive ability of MGC803 cells compared with the vehicle-treated group (P<0.05). As MMP9 has been previously reported to have an important role in gastric cancer invasion (17), the present study also investigated the expression level of MMP9 protein by western blot analysis and demonstrated that MMP9 expression was significantly downregulated in the OZ treatment group compared with the vehicle treatment group (P<0.05; Fig. 5C).…”
Section: Resultsmentioning
confidence: 69%
“…These findings may elucidated the underlying mechanism whereby OZ functions as a tumor suppressor by inducing apoptosis. In addition, previous reports indicated that MMP9, which is regulated by NF-κB (40), had an important role in the invasion of gastric cancer cells (17,41). The current study demonstrated that OZ significantly inhibited the expression of MMP9, which may be one of the molecular mechanisms by which OZ inhibited the invasion of gastric cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…It was used in scientific research to explore the physical or pathological functions, especially antitumour activities of NTS/NTSR1 signaling. In addition, SR48692 showed antitumour activities in multiple tumours, including melanoma (Zhang et al , 2014), prostate cancer (Baxendale et al , 2013), gastric cancer (Akter et al , 2015), pancreatic carcinoma (Iwase et al , 1997) and so on. These evidences indicated that SR48692 might be a potent drug for cancer treatments.…”
Section: Discussionmentioning
confidence: 99%